Association of Sugar-Sweetened Beverages (SSBs) consumption and sedentary behavior with prediabetes among adolescents - Putri Diajeng Lorenza; Farida Wahyu Ningtyias; Septy Handayani (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2026)
ABSTRACTBackground: Prediabetes is a borderline glycemic condition that indicates an increased risk of progression to type 2 diabetes mellitus. Prediabetes in adolescent is increasing along with economic development, nutritional transition, and sedentary behavior. Nutritional transition characterized by frequent intake of sugar-sweetened beverages (SSBs) and increased sedentary behavior has contributed to the rising risk of prediabetes among Indonesian adolescents. Without appropriate intervention, prediabetes is likely to develop into diabetes mellitus.Objectives: To examine the association between SSBs consumption and sedentary behavior with adolescents’ prediabetes, as a basis for early detection and timely intervention.Materials and Methods: This study is an analytical observational study with a cross-sectional design involving 146 adolescents from 9 senior high schools in the service areas of the Jember Kidul Community Health Center and the Lojejer Community Health Center. The variables studied included the frequency and consumption of SSBs measured using SQ-FFQ, sedentary behavior measured using ASAQ, and fasting blood glucose levels measured with Easy-touch GCU glucometer after an-8 hour fast. The data were analyzed using Spearman correlation with statistical software. This study received ethical approval under number 2966/UN25.8/KEPK/DL/2025.Results: Milk-flavored drinks were the most frequently consumed SSBs type (90.4%), while energy drinks were the least (10.2%). The most common sedentary behavior was using computer for fun (4.3 hours/day), while the least was worship-related activities (0.8 hours/day). The results showed a significant associationbetween adolescent prediabetes and the frequency of SSBs consumption (p <0.001), sugar intake from SSBs (p <0.001) and sedentary behavior (p <0.001).Conclusion: Consumption of SSBs and sedentary behavior are associated with prediabetes in adolescents. Therefore, early screening and education on prediabetes are needed in the healthcare sector and in schools.Keywords: Adolescent; prediabetes; sedentary behavior; sugar sweetened beverages